Changes of red blood cell rheology in newborns with congenital hypothyroidism during treatment. (October 2013) - Akin, Mustafa Ali; Aydogan, Sami; Gunes, Tamer; Artis, A. Seda; Karakukcu, Musa; Kurtoglu, Selim
Abstract Aim: We aimed to evaluate the deformability characteristics of RBC and the affecting factors in newborns diagnosed with congenital hypothyroidism (CH) and to compare the outcomes after the l-thyroxin treatment. Patients and methods: Enrolled subjects were divided into two subgroups as "patients" and age-matched healthy "controls". First blood samples were taken from all subjects for measuring elongation index (rEI) and osmotic fragility of RBC (OF), hematic and biochemical analytes affecting the RBC deformability in the neonatal age. All parameters were repeated a month after provided euthyroid state following the treatment in patients and age-matched healthy controls. Results: There was no difference between both groups in terms of complete blood count parameters and serum analytes (albumin, bilirubin and fibrinogen) except expected age-related changes in the first and second readings. Serum lipid/lipoprotein levels of both groups remained unchanged except triglyceride levels during the study period. The rEI of the patients were lower than that of controls in the first and second readings. The rEIs of the patients became increased, reaching (not equal) the levels of their controls during l-thyroxin treatment. Osmotic fragility of the patients was detected as lower than controls in the first and second readings, and became better during l-thyroxin treatment. Conclusion: Our results indicate that some changes may occur on the hematic and biochemical analytes affecting the RBC deformability features. Neonates with CH have the worst rEI initially, but they reached the indices of the healthy infants thanks to l-thyroxin treatment. Also, their OF features have been improved by l-thyroxin.